The Role of BRCA1 in the Cellular Response to Chemotherapy - Kennedy, Richard D.; Quinn, Jennifer E.; Mullan, Paul B.; Johnston, Patrick G.; Harkin, D. Paul (JNCI : Journal of the National Cancer Institute, 2004)
Germline mutations of the BRCA1 gene account for approximately 5% of breast and ovarian cancer cases, and lower than normal BRCA1 expression or function may be an important contributing factor in sporadic cancers. The major role of BRCA1 is to respond to DNA damage by participating in cellular pathways for DNA repair, mRNA transcription, cell cycle regulation, and protein ubiquitination. Because most chemotherapeutic agents function by directly or indirectly damaging DNA, the role of BRCA1 as a regulator of chemotherapy-induced DNA damage has been the subject of an increasing number of investigations. We review published preclinical and clinical evidence that the level of BRCA1 function in an individual patient's tumor can guide the choice of chemotherapeutic agents for breast and ovarian cancer. We conclude that a loss of BRCA1 function is associated with sensitivity to DNA-damaging chemotherapy and may also be associated with resistance to spindle poisons. We recommend that prospective clinical studies investigating the role of BRCA1 in the response to chemotherapy be conducted.